2017
DOI: 10.1021/acs.jafc.7b04273
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of an Insecticide Fenitrothion by Cunninghamella elegans ATCC36112

Abstract: In this study, the detailed metabolic pathways of fenitrothion (FNT), an organophosphorus insecticide by Cunninghamella elegans, were investigated. Approximately 81% of FNT was degraded within 5 days after treatment with concomitant accumulation of four metabolites (M1-M4). The four metabolites were separated by high-performance liquid chromatography, and their structures were identified by mass spectroscopy and/or nuclear magnetic resonance. M3 is confirmed to be an initial precursor of others and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Hydroxylation is an important way of pesticide metabolism by Cunninghamella elegans. 25,31,35 Similarly, hydroxylation may occur in M5 and M7, both of them had been reported in the previous studies. 31,36,37 So M5 and M7 were tentatively identied as hydroxydiazoxon and 2-hydroxylated diazoxon, respectively.…”
Section: Metabolism Of Diazinon By C Eleganssupporting
confidence: 70%
“…Hydroxylation is an important way of pesticide metabolism by Cunninghamella elegans. 25,31,35 Similarly, hydroxylation may occur in M5 and M7, both of them had been reported in the previous studies. 31,36,37 So M5 and M7 were tentatively identied as hydroxydiazoxon and 2-hydroxylated diazoxon, respectively.…”
Section: Metabolism Of Diazinon By C Eleganssupporting
confidence: 70%
“…Microorganisms have been studied extensively for their ability to degrade pesticides (Ayilara and Babalola 2023 ) and the same fungi described above are often employed in pesticide biotransformation and biodegradation studies. For example, C. elegans has been employed to degrade a range of pesticides including the pyrethroids cyhalothrin, transfluthrin and β-cyfluthrin (Khan and Murphy 2021 ; Palmer-Brown et al 2019 ), and the organophosphate pesticides fenitrothrion and diazinon (Zhao et al 2020 ; Zhu et al 2017 ). The degree of catabolism varies depending on the nature of the pesticide and the fungus employed, thus it is possible that in some cases metabolites that are potentially toxic can be produced.…”
Section: Pesticidesmentioning
confidence: 99%
“…PBO deactivates CYP by irreversible binding of the catalytic heme iron. In addition to mammalian studies, PBO was also reported to inhibit the fungal metabolism of pesticides (Zhu et al, 2010). Alkane degradation by Yarrowia involved a multiple enzyme-catalyzed metabolic pathway (e.g., CYPs, alcohol/aldehyde dehydrogenase, and many b-oxidation related enzymes) (Fickers et al, 2005).…”
Section: Effects Of Piperonyl Butoxidementioning
confidence: 99%